Develop ECE’s Virtuous Character by Designing Inspirative Storybook with Android-based Augmented Reality Application (Universitas Negeri Semarang, 2022)
Character education is a challenge for the current educational curriculum, especially how to develop an edutainment innovative learning model. The context of edutainment education for character education in children requires assistive media that acquire innovative learning models. The direction of this research is first to develop a fairy tale book equipped with Augmented Reality (AR) technology as a breakthrough form of innovative character education. Second, implementing AR technology products in the context of an independent curriculum for learning in children. The research results have developed a storybook as a fable built on 44 sub-stories that inspire virtuous humanist characters with the nuances of stories with local Indonesian characters. Storybooks are equipped with AR technology that can be downloaded via Google Playstore. Testing of storybook products is proven to build cognitive and affective aspects and mediate the presence of edutainment in the Merdeka Belajar curriculum. Keywords: Augmented Reality, Merdeka Belajar Curriculum, Innovative Learning, Character Education.